Displaying the Past in Byzantium. Figural Spolia on the City Gates of Nicaea (13th Century) - Bevilacqua, Livia (Actual Problems of Theory and History of Art, 2013)
In Anatolia during the Byzantine era, a number of cases are attested in which figural ‘spolia’ (i.e. pieces of ancient sculpture, stone carvings or reliefs) were reused in the building or restoration of the city walls and fortresses. Especially striking is the display of such ‘spolia’ as a part of the decoration of the main gates. In this paper, I will focus on the gates of the outer walls of the city of Nicaea (today Iznik), built during the reign of emperor John III Vatatzes (1222‒1254). This case is particularly interesting, since it is one of the richest examples surviving, in terms of the variety and size of the materials displayed. The gates must have created the strongest visual impact, at the time when Nicaea was regarded as the ‘temporary capital’ of the Byzantine Empire. A comparison will be carried out between the surviving works and the testimony of the written sources, both Byzantine and Western ones.